PERFORMANCE OF HYBRID RICE (ORYZA SATIVA L.) TO INTEGRATED NUTRIENT MANAGEMENT (INM) IN PARTIALLY RECLAIMED SODIC SOIL - VINOD KUMAR; A. K. S. PARIHAR; SANTOSH KUMAR; AJAY CHOURASIYA (The Bioscan, 2014)
A field experiment was carried out at Instructional Farm of Narendra Deva University of Agriculture and Technology, Narendra Nagar (Kumarganj), Faizabad (U.P.) during kharif, 2011 to study the performance of hybrid rice (Oryza sativa L.) to integrated nutrient management in partially reclaimed sodic soil. The experiment was laid out in Randomized Block Design with three replications. The seven treatments consisted with different integrated nutrient management combinations. The maximum plant height (113.73 cm), panicle length (19.67 cm), number of grains panicle-1 (75.10), test weight (23.20 g), grain yield (69.16 q ha-1) and straw yield (83.12 q ha-1) were recorded with 75% RDF + 25% FYM-N which were significantly superior over 75% RDF and 50% RDF + 50 % FYM-N, minimum was recorded with 100 % N through FYM. The higher N, (1.07%) P (0.27%) and K (1.02%) content were recorded with the application 75% RDF + 25% FYM-N followed by 100 % RDF. The maximum gross income (Rs. 70489.4 ha-1), net returns (Rs. 43242.61) ha-1 and B: C ratio (1.64) were recorded with the treatment 75% RDF + 25% FYM-N followed by the treatment 100 % RDF.